Feasibility of neck electrical impedance tomography to monitor upper airway dynamics during sleep - Piccin, Vivien S.; de Camargo, Erick D. L. B.; Andrade, Rafaela G. S.; Torsani, Vinícius; Schorr, Fabíola; Sardinha, Priscilla S.; Madeiro, Fernanda; Genta, Pedro R.; Gregório, Marcelo G.; de Carvalho, Carlos R. R.; Amato, Marcelo B. P.; Lorenzi-Filho, Geraldo (Frontiers in Sleep, 2023)
BACKGROUND: There is a lack of non-invasive methods for monitoring the upper airway patency during sleep. Electrical impedance tomography (EIT) is a non-invasive, radiation-free tool that has been validated to monitor lung ventilation. We hypothesized that electrical impedance tomography (EIT) can be used for monitoring upper airway patency during sleep. METHODS: Sleep was induced in 21 subjects (14 males, age 43 ± 13 years, body mass index 32.0 ± 5.3 kg/m2) with suspected obstructive sleep apnea (apnea-hypopnea index: 44 ± 37 events/h, range: 1-122 events/h) using low doses of midazolam. Patients wore a nasal mask attached to a modified CPAP device, allowing variable and controlled degrees of upper airway obstruction. Confirmation of upper airway patency was obtained with direct visualization of the upper airway using nasofibroscopy (n = 6). The changes in total neck impedance and in impedance in four cranio-caudal regions of interest (ROIs) were analyzed.. RESULTS: Total neck impedance varied in concert with breathing cycles and peaked during expiration in all patients. Group data showed a high cross-correlation between flow and impedance curves (r = -0.817, p < 0.001). Inspiratory peak flow correlated with simultaneous neck impedance (r = 0.866, p < 0.001). There was a high correlation between total neck impedance and velopharynx area (r = 0.884, p < 0.001), and total neck impedance and oropharynx area (r = 0.891, p < 0.001). CONCLUSIONS: Neck EIT is sensitive and captures pharyngeal obstruction under various conditions. Neck EIT is a promising method for real-time monitoring of the pharynx during sleep.